The Impact Of 6 February Earthquake On The Stock Returns In Damascus Securities Exchange (DSE) (An Event Study) - morheg, monzer (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This research investigated the effects of the 06.02.2023 earthquake as a natural disaster hits parts of Syria on daily stock returns of firms listed in Damascus securities exchange (DSE) by using an event study methodology to detect an abnormal returns around the event day. The data used consists of the stock close prices of firms listed in DSE and the Damascus securities exchange index (DWX) prices, it obtained from the website of DSE at: http://www.dse.gov.sy. The research found that there is a negative impact of earthquake on the stock prices/ returns of firms listed in DSE, and on market index prices in the post-event period, but its severity and time of occurrence differed for the sectors.